Implementation of Digital Product-Based Deep Learning with a Deep Learning Approach - Rohmaniyah, Vivid; Sapari, Imam; Sabara, Rahma; Banjar, Banjar; Haris, Abdul (Indonesian Journal of Teaching and Learning, 2025)
Purpose – This study aims to describe the concepts, implementation strategies, and impacts of digital product-based deep learning on student learning outcomes in the era of the Industrial Revolution 4.0 and Society 5.0. The background of this research lies in the demand for mastering 21st-century skills—critical, creative, collaborative, and communicative thinking—which requires a paradigm shift from mere knowledge transfer to meaningful and applicable learning. Methodology – This study employed a qualitative descriptive approach. Data were collected through literature review, observation of implementation, and interviews with teachers and students. The analysis was conducted descriptively to present the relationship between deep learning concepts, digital product-based implementation strategies, and their impacts on students’ competency achievement. Findings – The results indicate that the application of deep learning in modern education is implemented through contextual learning, project- or problem-based models, and the strengthening of 21st-century skills. Digital product-based implementation strategies include creative planning, the use of collaborative applications, strengthening the role of teachers as facilitators, and the adoption of authentic assessment. The impacts include improved conceptual understanding, higher-order thinking skills, creativity, and student learning motivation. Novelty – This study contributes by integrating digital product-based deep learning that incorporates interactive technologies such as videos, e-books, and educational applications, thereby expanding opportunities for meaningful learning in the 21st-century context. Significance – This research provides insights for teachers, curriculum developers, and education practitioners on innovative strategies to optimise the competencies of the digital generation while addressing learning challenges in the era of the Industrial Revolution 4.0 and Society 5.0.